FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI USIA DEWASA PADA MASA PANDEMI COVID-19 DI KELURAHAN PABUARAN CIBINONG BOGOR - Sifa Fauzi Marwah; Milla Evelianti Saputri; Tommy Jemmy Fransiscus Wowor (Universitas Sam Ratulangi, 2022)
Background: presence of the COVID-19 pandemic has an impact on all aspects, including development of hypertension. During COVID-19 pandemic, it certainly has an impact on people's psychology. It is very important to monitor these people because people with high blood pressure are in poor health and are at risk of dying if they become infected with COVID-19. Aim: of this study was to find out what factors were associated with incidence of hypertension in time pandemic Covid-19 in RW 12, Pabuaran Cibinong. The Method of this study used (Case Control). Sample size in this study was 78 people, consisting of 39 cases and 39 controls with a ratio between cases and controls of 1:1. The Results showed that there was a significant relationship between history of hypertension and incidence of hypertension adults with a p-value of 0.013, and stress factors with incidence of hypertension adults with a p-value of 0.027. Conclusion: This study concluded that there is a significant relationship between family history and factors stress with incidence of hypertension adults during COVID-19 pandemic in RW 12, Pabuaran Cibinong, Bogor. Therefore, it is recommended to the community, especially in people with hypertension to be able to control blood pressure and stress experienced.Keywords: Hypertension; COVID-19; Blood pressure